Indikasi Seksio Sesarea di RSUP Prof. Dr. R. D. Kandou Manado Tahun 2017 dan 2018 - Pamilangan, Edwin D.; Wantani, John J. E.; Lumentut, Anastasia M. (Universitas Sam Ratulangi, 2020)
Abstract: The prevalence of caesarian section (C-section) in Indonesia is increasing continuously from 7% reported by SDKI 2007 to 17% reported by SDKI 2017. This study was aimed to obtain the indication of C-section at Prof. Dr. R.D. Kandou Hospital Manado in years 2017 and 2018. This was a descriptive and retrospective study. The results showed that of total 2822 deliveries in 2017 and 2018, the C-section was performed on 694 patients (49.64%) in 2017 and on 736 patients (51.69%) in 2018. The most common maternal indication for C-section among 424 patients (42.7%) was previous C-section in 107 patients (25,23%) meanwhile the most common fetal indication among 379 patients (38.17%) was fetal distress in 205 patients (54.09%). Moreover, the most common combined indication among 190 patients (19.13%) were severe preeclampsia and fetal distress in 40 patients (21.05%). In conclusion, the most common indications of C-section were previous C-section, fetal distress, and of the combined indication were severe pre eclampsia and fetal distress.Keywords: C-section, maternal indication, fetal indication, combined indicationÂ Abstrak: Angka persalinan seksio sesarea di Indonesia terus meningkat, dengan persentase 7% pada SDKI 2007 menjadi 17% pada SDKI 2017 Penelitian ini bertujuan untuk mengetahui indikasi dilakukannya seksio sesarea di RSUP Prof. Dr. R.D. Kandou Manado tahun 2017 dan 2018. Jenis penelitian ialah deskriptif retrospektif. Hasil penelitian mendapatkan dari total 2822 persalinan pada tahun 2017 dan 2018, angka kejadian seksio sesarea ialah 694 pasien (49,64%) pada tahun 2017 dan 736 pasien (51,69%) pada tahun 2018. Indikasi ibu sebanyak 424 pasien (42,7%), paling banyak disebabkan oleh riwayat seksio sesarea sebelumnya sebanyak 107 pasien (25,23%). Indikasi janin sebanyak 379 pasien (38,17%), paling banyak disebabkan oleh gawat janin sebanyak 205 pasien (54,09%). Indikasi gabungan sebanyak 190 pasien (19,13%), paling banyak disebabkan oleh preeklamsi berat (PEB) dan gawat janin pada 40 pasien (21,05%). Simpulan penelitian ini ialah pada persalinan seksio sesarea, indikasi ibu terbanyak ialah riwayat seksio sesarea; indikasi janin terbanyak ialah gawat janin; dan indikasi gabungan terbanyak ialah preeklamsi berat dan gawat janin.Kata kunci: seksio sesarea, faktor ibu, faktor janin, faktor gabungan